Cambios en el diagnóstico miofuncional del hábito de deglución atípica compleja y simple durante los tratamientos de ortodoncia (2023)
This work is within the line of promotion and prevention of oral health of the specialization in orthodontics of the Faculty of Dentistry of the Antonio Nariño University. A series of analyzed studies have shown favorable results for Myofunctional Therapy (FMT), taking it into account as a treatment that can be performed in combination with maxillary orthopedics and orthodontics in the modification of malocclusions, oral habits, respiratory alterations, in the normal physiology of swallowing and breathing in such a way that by stabilizing these functional imbalances, a correction in body posture and foot print is also achieved due to the relationship they show (Bandyopadhyay et al., 2020).